A Comparison of Image-Guided Targeted Prostate Biopsy Outcomes by PI-RADS® Score and Ethnicity in a Diverse, Multiethnic Population. Issue 3 (21st September 2021) - Hines, Laena; Zhu, Denzel; DeMasi, Matt; Babar, Mustufa; Chernyak, Victoria; Kovac, Evan Z.; Aboumohamed, Ahmed; Sankin, Alex; Agalliu, Ilir; Watts, Kara L.
Abstract : Abstract : Purpose: NonHispanic Black (NHB) and Hispanic/Afro-Caribbean men have the highest risk of prostate cancer (PCa) compared to nonHispanic White (NHW) men. However, ethnicity-specific outcomes of targeted fusion biopsy (FB) for the detection of PCa are poorly characterized. We compared the outcomes of FB by Prostate Imaging Reporting and Data System (PI-RADS®) score and race/ethnicity among a diverse population. Materials and Methods: We evaluated all men who underwent image-guided FB for suspicious lesions on prostate magnetic resonance imaging (≥PI-RADS 3) over a 2-year period. We examined associations of race/ethnicity and PI-RADS score with risk of PCa or clinically significant PCa (cs-PCa, Gleason Group ≥2) on FB using mixed-effects logistic regression models. Results: A total of 410 men with 658 lesions were analyzed, with 201 (49.0%) identified as NHB and 125 (30.5%) identified as Hispanic. NHB men had a twofold increase in the odds of detecting cs-PCa (OR=2.7, p=0.045), while Hispanic men had similar odds of detecting cs-PCa compared to NHW men. With regard to all PCa, NHB men had a similar increase in the odds of detecting all PCa (OR=2.4, p=0.050), which was borderline statistically significant compared to NHW men on FB. When we excluded men on active surveillance, NHB men had even stronger associations with detection of cs-PCa (OR=3.10, p=0.047) or all PCa (OR=2.77, p=0.032) compared to NHW men. Conclusions: NHB men have higher odds for overall PCa and cs-PCa on FB compared to NHW men. Further work may clarify differences per PI-RADS score. Clinicians should interpret prostate magnetic resonance imaging lesions with more caution in NHB men.